RISK MANAGEMENT OF SHIP PASSENGER SERVICE OPERATIONAL OFFICERS USING THE HIRADC METHOD IN THE PORT INDUSTRY IN SURABAYA - Devi, Devi; Widajati, Noeroel (HEARTY, 2025)
Background: Our organization provides port services, including passenger services. carrying a range of human activity-related dangers that could harm employees' health at work. Accidents and industrial diseases can be avoided by evaluating the risks that exist right now and eliminating potential hazards at work. Purpose: Identifying hazards, conducting risk assessments, and controlling work operations for the ship service division's passenger service operating officers. Method: The data gathering method is based on both primary and secondary data, with primary data based on observations of the issue object in the field. Secondary data is data derived from data owned by the company. Meanwhile, identify and conduct hazard risk analysis utilizing the HIRADC approach, which is assessed in accordance with AS/NZS 4630:2004 and comprises three stages: Hazard Identification, Risk Assessment, and Determining Control.Result: The risk assessment identified 14 hazards, with 6 in the low-risk category, 6 in the medium-risk category, and 2 in the high-risk category. Conclusion: Several hazards were discovered during hazard identification in the operational passenger service officers discovered physical, biological, and ergonomic concerns, as well as psychological or behavioral factors that can pose a hazard.